Interactive Multimedia Website For Promoting Mumbul Sangeh Park As A Tourist Destination - Wiguna, I Putu Indra; Tonyjanto, Christian; Datya, Aulia Iefan; Kurniawijaya, Putu Andika (Information Technology and Science (ITScience), 2025)
Mumbul Sangeh Park in Bali has experienced low visitor turnout, primarily due to inadequate promotional strategies. To address this issue, a study was conducted to develop a modern, interactive promotional website aimed at increasing public awareness of the park’s historical significance and unique attractions. The website development followed a structured Software Development Life Cycle (SDLC) approach, specifically utilizing the waterfall model. The system was implemented using the PHP programming language, supported by the Laravel framework and a MySQL database. Functional verification was performed using black box testing to ensure all system features operated as intended. The resulting website is fully functional, responsive, and delivers comprehensive information. It also includes an intuitive administrative panel that enables park administrators to easily manage content updates, including photo galleries, news, and visitor information. The system represents a strategic digital initiative to enhance the visibility and reputation of Mumbul Sangeh Park in the era of digital tourism.